The Network Characteristic Analysis of Research Projects on International Research Cooperation - Noh, Younghee; Kim, Taeyoun; Chang, Rosa (International Journal of Knowledge Content Development & Technology, 2018)
In this study, the network analysis of researchers, institutions, and research principal agent was conducted to understand structure characteristics of international cooperation research project implemented from 1997 to 2018. The network of researchers and institutions were decentralized structure. On the other hands, the network of research principal agent was centralized structure. The Soul National University is the leading organization of international cooperation research project. In terms of research principal agent, corporation is the leading principal agent. In additions, the results of the network centroid analysis of the researchers and institutions were correlated with the research funds. As a result, it was confirmed that the network centroid of research organization was linearly related to research funds. URL: http://ijkcdt.net/xml/17764/17764.pdf